Analysis The Degree of Community Participation Possibility on Restoration Planning for Lowland Forest Landscape of Lepan Watershed - Langkat District - Hasibuan, Nurhayani; Samsuri; Gunawan Ahmad, Alfan (Talenta Publisher, 2019)
Watershed can become one of forest condition indicator. Lepan watershed belongs to main priority category in North Sumatera, the forest has a poor condition. This study aim to determine the degree of community participation possibility in the planning of restoration activities that will be done in Lepan watershed. This research used of the descriptif statitic analysis. The research shows that the possibility degree of community participation on forest landscape restoration activity is the high degree. The selection of the suitability of the plan species used is determined from the sum of the proportion of weight based on community perception and the analysis of natural forest vegetation.